Screening identifies suboptimal vaccination protection in illness-susceptible elite athletes - Turner, S. E.; Hull, J. H.; Jackson, A.; Loosemore, M.; Ranson, C.; Kelleher, P.; Shah, A. (Clinical Journal of Sport Medicine, 2021)
Objective: Some groups of elite athletes have an apparent increased susceptibility to respiratory tract infection (RTI) with implications for their health and athletic performance. In this study, we aim to systemically evaluate vaccine response patterns as a potentially efficacious intervention strategy in elite athletes preparing for Olympic competition. Design: Cross-sectional observational study. Setting: A UK Sport-funded Olympic training program. Patients: One hundred twenty elite athletes and 10 matched healthy controls were studied. A subset of athletes were classified as RTI highly susceptible (n = 22), RTI nonsusceptible (n = 23), and asthmatic (n = 33), with matched controls also recruited (n = 10, 27 ± 3 years). Interventions/outcome measure: Serum samples were analysed from participants analysing enzyme-linked immunosorbent assay for Immunoglobulin G (IgG) responses against measles, mumps, rubella, and pneumococcus vaccines. Results: Although a majority of athletes (>90%) had detectable IgG levels against measles and rubella, only 76% had detectable mumps responses, with similar findings apparent in controls. Of those RTI-susceptible and asthmatic athletes, 22% had suboptimal antipneumococcal responses below 30 mg/L. Conclusion: A significant proportion of elite athletes preparing for Olympic competition seem to be at risk of mumps infection. In addition, RTI-susceptible and asthmatic athletes exhibit suboptimal pneumococcal antibody responses, highlighting a need for prospective immune screening in athletes to ensure vaccination strategies are effectively delivered.